STRESS TOWARD NURSE AND QUALITY OF NURSING AT PROF.DR. H. ALOEI SABOE LOCAL PUBLIC HOSPITAL GORONTALO - ., Sarifuddin (Sainstek, 2008)
Stress at work place is not a strange phenomenon anymore. Stress can occur to anyone even to a nurse. Stress is said as over demand of individuals capability to fulfill such demand. Physical and psychological condition of the nurse is closely related to her performance. This study is aimed at notifying relation of nurses stress with quality of nursing. Sample of this study is nurses working at tropic side at about 15 people, purposively taken, using cloze questioner and observation sheet instruments. The analysis of data is done using Chi-Sguare (X2). Result of data analysis shows that: X2 count = 4,29 and X2 (0,005) (1) = 3,84 or X2c count > X2 (0,005) (1) there for it is concluded that there is relationship between the nurse stress and quality of nursing. In addition, there is information about stress cause of the nurse, it is stated that the cause mostly from patients and treatment upbringing, salary and the head and partners, and also entertainment to establish quality of nursing which is commonly good. Most nurse have made implementation, physical examination, nursing diagnosis, and evaluation